Biomechanical Analysis of the Forces Exerted during Different Occlusion Conditions following Bilateral Sagittal Split Osteotomy Treatment for Mandibular Deficiency - Yuan-Han Chang; Man-Yee Chan; Jui-Ting Hsu; Han-Yu Hsiao; Kuo-Chih Su (Applied Bionics and Biomechanics)
The bilateral sagittal split osteotomy (BSSO) technique is commonly used to correct mandibular deficiency. If the patient is exposed to excessive external forces after the procedure, occlusal changes or nonunion may occur. However, previous studies only focused on single external forces on the mandible and did not conduct relevant research on the forces exerted by different occlusion conditions. The main purpose of this study was to use finite element analysis methods to determine the biomechanics of four common occlusion conditions after BSSO surgical treatment. This study constructed a finite element analysis computer model of a miniplate implanted in the lower jaw. The structure of the model consisted of the mandible, miniplate, and screws. In addition, external forces were applied to the superficial masseter, deep masseter, medial pterygoid, anterior temporalis, middle temporalis, and posterior temporalis muscles to simulate the incisal clench, intercuspal position (ICP), right unilateral molar clench (RMOL), and right group function occlusion conditions. Subsequently, this study observed the effects of these conditions on the miniplate, screws, and mandible, including the von Mises stress values. The results showed that all of the different occlusion conditions that this study evaluated placed high stress on the miniplate. In the ICP and RMOL occlusion conditions, the overall mandibular structure experienced very high stress. The screw on the proximal segment near the bone gap experienced high stress, as did the screw on the buccal side. According to the present analysis, although the data were not directly obtained from clinical practice, the finite element analysis could evaluate the trend of results under different external forces. The result of this study recommended that patients without intermaxillary fixation avoid the ICP and RMOL occlusion conditions. It can be used as a pilot study in the future for providing clinicians more information on the biomechanics of implantation.